Prayer for a child - Field, Rachel, 1894-1942.; Jones, Elizabeth Orton, 1910-2005. (New York : Macmillan, 1944)
A prayer orginally written by the author for her daughter.
Maine author. Field summered as an adult on Sutton's Island, one of the Cranberry Isles off of Mount Desert.
Caldecott Medal, 1945.
Keywords: Prayers